Nuclear dynamics of influenza A virus ribonucleoproteins revealed by live-cell imaging studies. - Loucaides, E; von Kirchbach, J; Foeglein, A; Sharps, J; Fodor, E; Digard, P (2009)
The negative sense RNA genome of influenza A virus is transcribed and replicated in the nuclei of infected cells by the viral RNA polymerase. Only four viral polypeptides are required but multiple cellular components are potentially involved. We used fluorescence recovery after photobleaching (FRAP) to characterise the dynamics of GFP-tagged viral ribonucleoprotein (RNP) components in living cells. The nucleoprotein (NP) displayed very slow mobility that significantly increased on formation of transcriptionally active RNPs. Conversely, single or dimeric polymerase subunits showed fast nuclear dynamics that decreased upon formation of heterotrimers, suggesting increased interaction of the full polymerase complex with a relatively immobile cellular component(s). Treatment with inhibitors of cellular transcription indicated that in part, this reflected an interaction with cellular RNA polymerase II. Analysis of mutated influenza virus polymerase complexes further suggested that this was through an interaction between PB2 and RNA Pol II separate from PB2 cap-binding activity.